2016
DOI: 10.1007/s00266-016-0664-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Medical Chitosan on Capsular Formation Following Silicone Implant Insertion in a Rabbit Model

Abstract: This journal requires that authors assign a level of evidence to each submission to which Evidence-Based Medicine rankings are applicable. This excludes Review Articles, Book Reviews, and manuscripts that concern Basic Science, Animal Studies, Cadaver Studies, and Experimental Studies. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Our previous study demonstrated that carboxymethyl chitin could inhibit the expression of TIMP-1 in the capsule around silicone implants in a rabbit model. 16 Therefore, the inhibitory effect of carboxymethyl chitin on the expression of collagen type III in vivo might be related to the down-regulation of TIMP-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study demonstrated that carboxymethyl chitin could inhibit the expression of TIMP-1 in the capsule around silicone implants in a rabbit model. 16 Therefore, the inhibitory effect of carboxymethyl chitin on the expression of collagen type III in vivo might be related to the down-regulation of TIMP-1.…”
Section: Discussionmentioning
confidence: 99%
“…The results confirmed that carboxymethyl chitin decreased the thickness of the capsule at these three time points. 16 In this study, we chose 8 weeks as the observation time point because the capsular tissue was thicker at this time point than at the other two time points, and it is better to obtain ideal histologic specimens. However, to better understand the effect of carboxymethyl chitin on α-SMA and collagen expression in the capsular tissue, it is reasonable to include more time points, such as 4 weeks, 3 months, or even 6 months.…”
Section: Could Inhibit the Expressionmentioning
confidence: 99%
“…Previously, several preclinical studies using other AAAs, including poloxamer, 14 hyaluronate with carboxymethyl cellulose, 13,15,34 chitosan, 35 and amniotic fluid, 36 have been reported. Using a rat 13,34,36 or rabbit 14,15,35 model for conducting silicone implant insertion, previous studies demonstrated that the experimental group using AAA developed a thinner periprosthetic capsule than did the control group. As a further study based on several preclinical studies, we conducted the first prospective clinical study on the use of AAA in implant-based breast reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…83 Additionally, studies in animal models suggest that various medications such as Vitamin E, colchicine, botox, chitosan, collagenases, omega 3, and doxycycline could potentially be used to prevent the development of capsular contracture. [84][85][86][87][88][89][90] Despite the promise of these experimental therapies, most have not yet been explored in human trials. Continued investigations into novel therapies such as those described here are exciting and could help to substantially improve biologic response to implants and in turn reduce morbidity associated with periprosthetic fibrosis.…”
Section: Experimental/medical Preventionsmentioning
confidence: 99%